Historical, Geometrical, and Constructive Analyses of the Rotonda Roman Baths in Catania (Sicily) - Carola Tardo; Laura Floriano; Mariangela Liuzzo; Anna Maria Gueli; Giuseppe Stella; Giuseppe Margani (Buildings)
One of the main icons of the Roman civilisation are thermal baths, built as public places for personal hygiene, body and mind relaxation, recreation, social encounters, and sport. In Sicily, there is evidence of several thermal buildings dating back to the time of the Roman Empire. Notably, the “Terme della Rotonda”, in the city of Catania, have always attracted strong interest due to their intricate and fascinating architecture. However, at present the dating of the building remains within the complex is still uncertain, and diverse assumptions have been advanced on their original use. In this framework, this study presents the findings of a multidisciplinary research initiative aimed at advancing knowledge of this thermal complex. To this end, a 3D integrated survey of the complex was carried out, and architectural, typological, and construction analyses were conducted to examine the primary building elements. These investigations enabled us to provide detailed insights into the materials and construction techniques used, leading to a new hypothesis on the original layout of the thermal rooms. Additionally, a virtual platform of the archaeological site was developed to serve as a spatial information database, facilitating both scientific research and the dissemination of knowledge about the complex.